Topologically processed polymer solid electrolyte, battery and preparation method thereof
The topological processing of polymer PVDF-HFP is formed by forming the topological structure of borate dynamic covalent bonds, which solves the problem of insufficient conductivity and mechanical strength of polymer solid electrolytes in lithium batteries, and achieves a high-performance solid lithium battery.
Patent Information
- Application Number
- CN202510035365.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The application of polymer solid electrolytes in lithium batteries is limited by problems such as low ion conductivity, low ion migration number, and weak mechanical strength.
Through topological processing technology, polymer PVDF-HFP is used to dehydrofluorize and branch-graft the -OH group in an alkaline environment, and then react with phenylboric acid PhB to form a borate dynamic covalent bond, forming a polymer topological structure, promoting segment movement and increasing the electrolyte ionic conductivity.
The ionic conductivity and mechanical strength of the electrolyte are improved, the growth of lithium dendrites is inhibited, and a solid-state lithium battery with excellent circulation performance and long-term stability is obtained.
Smart Images

Figure CN119833743A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion battery, in particular to a topologically processed polymer solid electrolyte, a battery and a preparation method thereof. Background Art
[0002] With the rapid development of lithium-ion battery-related technologies, diversified energy storage needs continue to emerge, and people have put forward higher requirements for future lithium-ion batteries. Limited by safety hazards, such as the growth of lithium dendrites and the flammability and leakage of liquid electrolytes, solid electrolytes, especially solid polymer electrolytes, have attracted attention due to their high flexibility, good interfacial compatibility and scalability. However, polymer solid electrolytes still have problems such as low ion conductivity, low ion migration number, and weak mechanical strength, which limit their application in lithium batteries.
[0003] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0004] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide a topologically processed polymer solid electrolyte, a battery and a preparation method thereof.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A topologically processed polymer solid electrolyte comprises a polymer PVDF-HFP, a lithium salt, LiOH·H2O providing an alkaline environment, and a grafting reactant phenylboronic acid PhB; the mass ratio of the polymer PVDF-HFP to the lithium salt is configured to an effective amount that allows the lithium salt to fully dissolve and form a uniform mixture with the polymer; the molar ratio of LiOH·H2O to the polymer PVDF-HFP is configured to an effective amount that provides a sufficient alkaline environment to promote polymer dehydrofluorination and grafting -OH groups; and the addition amount of the grafting reactant phenylboronic acid PhB is configured to an effective amount that reacts with the polymer grafting group to form a borate ester dynamic covalent bond and optimizes the electrolyte ion conductivity.
[0007] Furthermore, the lithium salt is LiTFSI, and the organic solvent is N,N-dimethylformamide DMF.
[0008] Furthermore, the mass ratio of the polymer PVDF-HFP to the lithium salt is 1:(0.5-1); the molar ratio of the LiOH·H2O providing the alkaline environment to the polymer PVDF-HFP is (0.5-2):10; and the grafting reactant phenylboronic acid PhB is 5-25% of the mass of the polymer PVDF-HFP.
[0009] Furthermore, the grafting reactant phenylboronic acid PhB is 15% of the mass of the polymer PVDF-HFP.
[0010] A method for preparing a topologically processed polymer solid electrolyte comprises the following steps:
[0011] S1, obtaining a homogeneous polymer solution, adding the polymer PVDF-HFP and the lithium salt LiTFSI into an organic solvent and mixing and stirring to make the lithium salt and the polymer uniformly mixed;
[0012] S2, adding LiOH·H2O to the homogeneous polymer solution to configure an alkaline topological grafting environment, grafting -OH groups on the polymer, and then adding the grafting reactant phenylboronic acid PhB to continue mixing and stirring, reacting with the polymer grafting groups to chemically crosslink to form borate ester dynamic covalent bonds to obtain a polymer solid electrolyte precursor solution with a topological structure;
[0013] S3: pouring and leveling the polymer solid electrolyte precursor solution with the topological structure, and vacuum drying to obtain the topologically processed polymer solid electrolyte.
[0014] Furthermore, the lithium salt is LiTFSI, and the organic solvent is N,N-dimethylformamide DMF.
[0015] Furthermore, the mass ratio of the polymer PVDF-HFP to the lithium salt is 1:(0.5-1); the molar ratio of the LiOH·H2O providing the alkaline environment to the polymer PVDF-HFP is (0.5-2):10; the grafting reactant phenylboronic acid PhB is 5-25% of the mass of the polymer PVDF-HFP, preferably 15%.
[0016] A battery comprises a positive electrode sheet, a negative electrode sheet and the topologically processed polymer solid electrolyte.
[0017] Furthermore, the negative electrode sheet is a lithium sheet.
[0018] Furthermore, the topologically processed polymer solid electrolyte is used after being soaked in a common electrolyte for 3-6 hours.
[0019] The present invention has the following beneficial effects:
[0020] The present invention provides a topologically processed polymer solid electrolyte, a battery and a preparation method thereof, wherein the polymer PVDF-HFP is used to generate a C=C double bond by dehydrofluorination in an alkaline environment provided by LiOH·H2O, and then the (-OH) group is continuously grafted and reacted with phenylboronic acid PhB to form a borate ester, thereby forming a polymer topological structure to promote the movement of polymer chain segments and increase the electrolyte ion conductivity. The preparation method is simple and efficient. For its application, a continuous SEI film composed of lithium borate, lithium fluoride and some organic compounds will be formed on the surface of the lithium anode, which has strong mechanical strength, can effectively prevent unnecessary side reactions between lithium and the electrolyte, and inhibit the growth of lithium dendrites, thereby obtaining a solid-state lithium battery with excellent cycle performance and long-term stability.
[0021] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The critical performance diagrams are for Comparative Example 1 and Examples 1-5.
[0023] Figure 2 This is the XRD pattern of phenylboronic acid PhB.
[0024] Figure 3 These are the XRD diagrams of Comparative Example 1 and Examples 1-5.
[0025] Figure 4 It is a cycle performance diagram of comparative example 1 and example 3 under 0.5C charge and discharge conditions.
[0026] Figure 5 The impedance diagrams of Comparative Example 1 and Example 3 at 25°C.
[0027] Figure 6 The ionic conductivity and fitted Arrhenius plots of Comparative Example 1 and Example 3 at different temperatures.
[0028] Figure 7 For Comparative Example 1 and Example 3 at 1 mA cm -2 Diagram of lithium symmetry performance under cycling conditions. DETAILED DESCRIPTION
[0029] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0030] Ordinary polymer solid electrolytes still have problems such as low ion conductivity, low ion migration number, and weak mechanical strength, which limit their application in lithium batteries. The present invention provides a topologically processed polymer solid electrolyte and a preparation method thereof, which utilizes the property of polymer PVDF-HFP that it is easy to undergo dehydrogenation fluorination grafting -OH groups in an alkaline environment, introduces borate bonds, topologically transforms long-chain PVDF-HFP, promotes the movement of chain segments, and enhances the stability of the electrolyte.
[0031] The embodiment of the present invention provides a topologically processed polymer solid electrolyte, comprising a polymer PVDF-HFP, a lithium salt, LiOH·H2O providing an alkaline environment, and a grafting reactant phenylboronic acid PhB; the mass ratio of the polymer PVDF-HFP to the lithium salt is configured to be an effective amount that allows the lithium salt to fully dissolve and form a uniform mixture with the polymer; the molar ratio of LiOH·H2O to the polymer PVDF-HFP is configured to be an effective amount that provides a sufficient alkaline environment to promote dehydrofluorination of the polymer and grafting -OH groups; the added amount of the grafting reactant phenylboronic acid PhB is configured to be an effective amount that reacts with the polymer grafting group to form a borate ester dynamic covalent bond and optimizes the electrolyte ion conductivity.
[0032] In a preferred embodiment, the lithium salt is LiTFSI, and the organic solvent is N,N-dimethylformamide DMF.
[0033] In a preferred embodiment, the mass ratio of the polymer PVDF-HFP to the lithium salt is 1:(0.5-1), preferably 1:0.8; the molar ratio of the LiOH·H2O providing the alkaline environment to the polymer PVDF-HFP is (0.5-2):10, preferably 1:10; the grafting reactant phenylboronic acid PhB is 5-25% of the mass of the polymer PVDF-HFP, preferably 15%.
[0034] The embodiment of the present invention further provides a method for preparing the topologically processed polymer solid electrolyte, comprising the following steps:
[0035] S1, obtaining a homogeneous polymer solution, adding the polymer PVDF-HFP and the lithium salt LiTFSI into an organic solvent and mixing and stirring to make the lithium salt and the polymer uniformly mixed;
[0036] S2, adding LiOH·H2O to the homogeneous polymer solution to configure an alkaline topological grafting environment, grafting -OH groups on the polymer, and then adding the grafting reactant phenylboronic acid PhB to continue mixing and stirring, reacting with the polymer grafting groups to chemically crosslink to form borate ester dynamic covalent bonds to obtain a polymer solid electrolyte precursor solution with a topological structure;
[0037] S3: pouring and leveling the polymer solid electrolyte precursor solution with the topological structure, and vacuum drying to obtain the topologically processed polymer solid electrolyte.
[0038] The embodiment of the present invention further provides a battery, comprising a positive electrode sheet, a negative electrode sheet and the topologically processed polymer solid electrolyte. Preferably, the topologically processed polymer solid electrolyte is used after being soaked in a common electrolyte for 3-6 hours. Preferably, the negative electrode sheet can be a lithium sheet.
[0039] The polymer PVDF-HFP has the advantage of high conductivity. It is easy to undergo dehydrogenation and fluorination to generate C=C double bonds in an alkaline environment, and continue to react and continuously graft -OH groups. The present invention utilizes this characteristic, utilizes the -OH group and its alkaline environment to topologically modify the chain polymer chain, and introduces borate ester bonds. The characteristics of the polymer are changed, the movement of the chain segments is promoted, and the stability of the electrolyte is enhanced. Compared with the prior art, the present invention utilizes the characteristics of the polymer to create an alkaline environment to utilize the grafted -OH group to react with phenylboronic acid, and after topological processing, the movement of the internal chain segments of the electrolyte is accelerated, and the ionic conductivity of the electrolyte is improved. In addition, the dehydrogenated fluorinated polymer and the topologically increased phenylboronic acid can provide a continuous SEI film composed of lithium borate, lithium fluoride and some organic compounds for the lithium anode in the lithium battery, inhibiting the growth of lithium dendrites, thereby obtaining an all-solid-state metal lithium battery with excellent cycle performance and long-term stability. The preparation method of the present invention is simple and efficient.
[0040] The specific embodiments of the present invention are further described below.
[0041] In one embodiment, a method for preparing a polymer solid electrolyte with a topological structure comprises the following steps:
[0042] (1) obtaining a homogeneous polymer solution, adding the polymer PVDF-HFP and the lithium salt LiTFSI into the organic solvent DMF and mixing and stirring for 12 hours to make the lithium salt and the polymer evenly mixed;
[0043] (2) Topological grafting, adding LiOH·H2O to the homogeneous polymer solution and stirring at room temperature for 6 hours to configure an alkaline topological grafting environment, so as to graft -OH groups on the polymer. Then, adding the grafting reactant phenylboronic acid PhB and continuing to mix and stir for 6 hours, reacting with the polymer grafting group to chemically crosslink and form borate ester dynamic covalent bonds to obtain a polymer solid electrolyte precursor solution with a topological structure;
[0044] (3) vacuum drying: pouring the polymer solid electrolyte precursor solution with the topological structure onto a culture dish or a glass plate for automatic leveling, placing it into a vacuum drying oven at 80° C. for 12 h to obtain a topologically processed polymer solid electrolyte.
[0045] In one embodiment, in step (1), the polymer PVDF-HFP is 0.9 g, the lithium salt LiTFSI is 0.6 g, and the solvent DMF is 7.5 mL.
[0046] In one embodiment, the molar ratio of LiOH·H2O to polymer PVDF-HFP in step (2) is 1:10. The amount of grafting reactant phenylboronic acid PhB added is 5-25% of the mass of polymer PVDF-HFP.
[0047] In one embodiment, a battery preparation method using a topologically processed polymer solid electrolyte as a separator to replace a lithium-ion battery comprises the following steps:
[0048] The topologically processed polymer solid electrolyte sheets are cut and assembled into a lithium symmetrical battery in a glove box filled with Ar gas in the order of positive electrode shell, lithium sheet, electrolyte membrane, lithium sheet, gasket, spring sheet and negative electrode shell.
[0049] In one embodiment, the positive electrode sheet is prepared by uniformly mixing LFP, PVDF, and Super P at a mass ratio of 8:1:1, adding the mixture into NMP for slurry preparation, and coating the mixture on Al foil and drying the mixture to prepare an LFP positive electrode sheet.
[0050] Examples 1-5
[0051] The preparation method of a topologically processed polymer solid electrolyte in which the polymer is PVDF-HFP, the lithium salt is LiTFSI, the grafting reactant is phenylboronic acid PhB, the solvent is DMF, and LiOH·H2O provides an alkaline environment comprises the following steps:
[0052] (1) Weigh 0.9 g PVDF-HFP and 0.6 g LiTFSI into 7.5 mL DMF solution and stir for 12 h to mix the lithium salt and polymer evenly.
[0053] (2) Weigh 0.0176 g of LiOH·H2O and add it to the solution in (1), stir at room temperature for 6 hours, and the polymer PVDF-HFP is grafted with -OH groups. Then add the grafting reactant phenylboronic acid PhB and continue mixing and stirring for 6 hours. The amount of phenylboronic acid PhB in each example is 5%, 10%, 15%, 20%, and 25% of the mass of the polymer PVDF-HFP respectively;
[0054] (3) The electrolyte precursor solution in (2) is poured onto a culture dish or a glass plate for automatic leveling, and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a topologically processed polymer solid electrolyte.
[0055] Comparative Example 1
[0056] The method for preparing a polymer solid electrolyte without topological processing, wherein the polymer is PVDF-HFP, the lithium salt is LiTFSI, and the solvent is DMF, comprises the following steps:
[0057] (1) Weigh 0.9 g PVDF-HFP and 0.6 g LiTFSI into 7.5 mL DMF solution and stir for 12 h to mix the lithium salt and polymer evenly.
[0058] (2) The electrolyte precursor solution in (1) is poured on a culture dish or a glass plate for automatic leveling, and then placed in a vacuum drying oven at 80° C. for 12 h to obtain a polymer solid electrolyte without topological processing.
[0059] The polymer electrolyte membranes prepared in the above embodiments and comparative examples were subjected to critical current density tests to obtain the maximum current that the electrolyte can withstand under gradually increasing current conditions. The specific operation process is as follows: the polymer electrolyte membrane is sandwiched between two lithium sheets and assembled into a button battery. Then, the maximum current that the button battery can withstand under gradually increasing current conditions is compared using a blue battery test system. The test results are shown in Table 1.
[0060] Table 1
[0061]
[0062] As shown in Table 1, the maximum current that can be sustained under gradually increasing current conditions is significantly different when different amounts of phenylboronic acid PhB are added in Examples 1-5, among which Example 3 with an addition amount of 15% can withstand the maximum current and the best critical performance. With the addition of PhB, a LiF / Li-BO-rich SEI layer is formed in situ on the surface of the lithium anode, enhancing the mechanical strength of the SEI film and improving the critical performance. And the addition of an appropriate amount of phenylboronic acid PhB can play a better role.
[0063] The polymer electrolyte membranes prepared in the preferred embodiment 3 and comparative example 1 were subjected to electrochemical performance tests to obtain the long cycle performance of the electrolyte under 0.5C charge and discharge conditions. The specific operation process is as follows: the polymer electrolyte membrane is sandwiched between the positive electrode and the lithium sheet to assemble into a button battery. Then, the discharge capacity of the button battery under 0.5C charge and discharge conditions is tested for 200 weeks using a blue battery test system to compare its cycle performance. The test results are shown in Table 2.
[0064] Table 2
[0065]
[0066]
[0067] As shown in Table 2, after 200 cycles of 0.5C constant current charge and discharge, the capacity retention rate of the electrolyte in Comparative Example 1 and Example 3 is significantly different. The capacity of Example 3 with an addition amount of 15% is still 147.5 mAh·g after 200 cycles. -1 , the cycle performance is the best. Compared with comparative example 1, after topological processing, Example 3 promotes the movement of polymer segments, accelerates the transport of lithium ions in the electrolyte, and the electrochemical performance is greatly improved.
[0068] Figure 1 It is the critical performance diagram of comparative example 1 and embodiments 1-5.
[0069] Figure 2 This is the XRD pattern of phenylboronic acid PhB.
[0070] Figure 3 The XRD diagrams of Comparative Example 1 and Examples 1-5 show that the crystalline peaks of PVDF-HFP in Examples 1-5 are all decreased, indicating that more amorphous regions are generated after topological grafting of phenylboronic acid PhB, which promotes the segmental movement of the polymer.
[0071] Figure 4 It is a cycle performance diagram of comparative example 1 and example 3 under 0.5C charge and discharge conditions.
[0072] Figure 5 The impedance diagram of comparative example 1 and example 3 at 25°C is as follows: the polymer electrolyte membrane is sandwiched between two stainless steel sheets to assemble a button battery. The AC impedance test is performed using a CHI660E electrochemical workstation. During the test, the amplitude is set to 10mV and the scanning frequency range is 0.1Hz to 10 5 Hz. By calculation, at 25°C, the ionic conductivity of Comparative Example 1 is 0.89×10 -3 S cm -1 , while the ionic conductivity of the polymer electrolyte after topological processing in Example 3 can reach 1.52×10 -3 S cm -1 .
[0073] Figure 6 The ionic conductivity and fitted Arrhenius plots at different temperatures of Comparative Example 1 and Example 3. The ionic conductivity of Example 3 is greater than that of Comparative Example 1 at any temperature, and the activation energy of ion migration in Example 3 is less than that in Comparative Example 1, indicating that the topological electrolyte can enable Li+ to conduct rapidly in the electrolyte.
[0074] Figure 7 For Comparative Example 1 and Example 3 at 1 mA cm -2Figure 2. Lithium symmetry performance diagram under cycling conditions. The specific operation process is as follows: the polymer electrolyte membrane is sandwiched between two lithium sheets to assemble a button cell. Then, the button cell is tested at 1 mA cm using the Blue Battery Test System. -2 The performance of the embodiment 3 is compared with that of the embodiment 4. Figure 6 The results of the electrolyte activation energy Ea confirm each other, and compared with Comparative Example 1, Example 3 can well suppress lithium dendrites.
[0075] In summary, the advantages of the present invention compared with the prior art are:
[0076] Compared with the prior art, the topologically processed polymer solid electrolyte of the present invention utilizes polymer characteristics to topologically modify the chain polymer, promotes the movement of chain segments, and increases ionic conductivity. At the same time, a more stable SEI is constructed through the phenylboronic acid PhB bond to effectively protect the lithium negative electrode. Thus, an all-solid-state metal lithium battery with excellent cycle performance and long-term stability is obtained. The preparation process of the present invention is simple and efficient.
[0077] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A topologically processed polymer solid electrolyte, characterized in that: The invention comprises a polymer PVDF-HFP, a lithium salt, LiOH·H2O providing an alkaline environment, and a grafting reactant phenylboronic acid PhB; the mass ratio of the polymer PVDF-HFP to the lithium salt is configured to be an effective amount so that the lithium salt is fully dissolved and forms a uniform mixture with the polymer; the molar ratio of the LiOH·H2O to the polymer PVDF-HFP is configured to be an effective amount so as to provide a sufficient alkaline environment to promote dehydrofluorination of the polymer and grafting -OH groups; and the addition amount of the grafting reactant phenylboronic acid PhB is configured to be an effective amount so as to react with the polymer grafting group to form a borate ester dynamic covalent bond and optimize the electrolyte ion conductivity.
2. The topologically processed polymer solid electrolyte according to claim 1, characterized in that: The lithium salt is LiTFSI, and the organic solvent is N,N-dimethylformamide DMF.
3. The topologically processed polymer solid electrolyte according to claim 1 or 2, characterized in that: The mass ratio of the polymer PVDF-HFP to the lithium salt is 1:(0.5-1); the molar ratio of the LiOH·H2O providing the alkaline environment to the polymer PVDF-HFP is (0.5-2):10; the grafting reactant phenylboronic acid PhB is 5-25% of the mass of the polymer PVDF-HFP.
4. The topologically processed polymer solid electrolyte according to claim 1, characterized in that The grafting reactant phenylboronic acid PhB accounts for 15% of the mass of the polymer PVDF-HFP.
5. A method for preparing a topologically processed polymer solid electrolyte, characterized in that: The following steps are involved: S1, obtaining a homogeneous polymer solution, adding the polymer PVDF-HFP and the lithium salt LiTFSI into an organic solvent and mixing and stirring to make the lithium salt and the polymer uniformly mixed; S2, adding LiOH·H2O to the homogeneous polymer solution to configure an alkaline topological grafting environment, grafting -OH groups on the polymer, and then adding the grafting reactant phenylboronic acid PhB to continue mixing and stirring, reacting with the polymer grafting groups to chemically crosslink to form borate ester dynamic covalent bonds to obtain a polymer solid electrolyte precursor solution with a topological structure; S3: pouring and leveling the polymer solid electrolyte precursor solution with the topological structure, and vacuum drying to obtain the topologically processed polymer solid electrolyte.
6. The method for preparing a topologically processed polymer solid electrolyte according to claim 5, characterized in that: The lithium salt is LiTFSI, and the organic solvent is N,N-dimethylformamide DMF.
7. The method for preparing a topologically processed polymer solid electrolyte according to claim 5 or 6, characterized in that: The mass ratio of the polymer PVDF-HFP to the lithium salt is 1:(0.5-1); the molar ratio of the LiOH·H2O providing the alkaline environment to the polymer PVDF-HFP is (0.5-2):10; the grafting reactant phenylboronic acid PhB is 5-25% of the mass of the polymer PVDF-HFP, preferably 15%.
8. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a topologically processed polymer solid electrolyte as claimed in any one of claims 1 to 4.
9. The battery according to claim 8, characterized in that The negative electrode sheet is a lithium sheet.
10. The battery according to claim 8 or 9, characterized in that The topologically processed polymer solid electrolyte is used after being soaked in a common electrolyte for 3-6 hours.
Citation Information
Patent Citations
Boron-containing solid polymer electrolyte and preparation method and application thereof
CN106229547A
All-solid-state polymer electrolyte with self-healing function and preparation method thereof
CN111477953A
Polymer solid electrolyte containing 2, 3, 4, 5, 6-pentafluorophenylboronic acid and all-solid-state metal lithium battery
CN115020818A
Topological structure all-solid-state polymer electrolyte and preparation method and application thereof
CN115882060A
Composite polymer solid electrolyte, battery and preparation method thereof
CN118136928A